Pattern of internet use for pregnancy-related information and its predictors among women visiting primary healthcare in Qatar: a cross-sectional study - Ayman Al-Dahshan (BMC, 2021)
Abstract Background Internet usage has been steadily increasing and the available online information for pregnant women today is immense. Objective This study aimed to investigate the prevalence of women who search for information relating to pregnancy on the internet and to identify predictors of this behavior among expecting women visiting primary health care (PHC) centers in Qatar. Methods A cross-sectional study was conducted at the antenatal clinics of six PHC centers in Qatar from June 1 to December 31, 2019. Pregnant women were recruited through a systematic random sampling technique. Participants were interviewed using a structured questionnaire. Descriptive and analytic statistics were used when appropriate. A multivariable logistic regression analysis was constructed to identify the predictors of internet use for pregnancy-related information. Results The study included 403 pregnant women (response rate: 87.9%). Most of them were in the 26–35 years age category (71.5%), in the second trimester (55.5%), and had 1–2 children at home (51.5%). The internet was the most common source (81.1%) of pregnancy-related information. The access to online information was mainly through websites (67.3%), mobile applications (48.3%), and social media platforms (39.7%). The most frequently searched topics online were fetal development (74.3%), diet during pregnancy (53.6%), and management of health problems (39.6%). The multivariable regression model identified the age group 26–35 years (AOR: 4.93; 95% CI: 2.14, 11.38), Arabs (AOR: 4.12; 95% CI: 2.03, 8.36), tertiary education (AOR: 5.22; 95% CI: 1.78, 15.33), being a housewife (AOR: 6.37; 95% CI: 1.44, 28.19), or employed (AOR: 5.56 95% CI: 1.31, 23.63), and having up to 2 children as independent predictors of internet use for pregnancy-related information. Conclusion The internet was a commonly used source of health information among pregnant women in Qatar. Internet use was significantly associated with the age group of 26–35 years, Arabs, higher level of education, being employed or a housewife, and having up to two children.